Management of recovery processes in pre-competitive training of longdistance runners (Eurasian Research Bulletin, 2025)
In this article, we examine the relationship between loading and recovery during the precompetitive training of ultra-distance runners. In the article, it is highlighted that the correctly chosen method and efficient management of recovery are one of the main factors for achieving high results in sports competitions. The balance between training load and recovery to achieve high results is supported by scientific evidence.